2020
DOI: 10.31557/apjcp.2020.21.10.3061
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward and Knowledge of Colorectal Cancer Screening among an Omani Adult Population Attending a Teaching Hospital

Abstract: Objective: Colorectal cancer (CRC) is the third most commonly diagnosed cancer in Oman after breast and thyroid. Awareness regarding the availability of CRC screening services could play a major role in promoting early detection and reducing mortality rates. The aim of this study was to identify public knowledge and attitudes toward CRC screening. Methods: This cross-sectional study was conducted among 410 members of the public attending the Sultan Qaboos University Hospital in Muscat, Oman. A questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Although patients' awareness of CRC in Oman was low, they were willing to undergo a screening test if advised by their doctor [20]. In the same study, the authors identified emotional and cultural barriers that older Omani men and women faced regarding CRC screening and advised further efforts to tackle these issues.…”
Section: Criteria 6: Is There Interest In Informed Deliberation About...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients' awareness of CRC in Oman was low, they were willing to undergo a screening test if advised by their doctor [20]. In the same study, the authors identified emotional and cultural barriers that older Omani men and women faced regarding CRC screening and advised further efforts to tackle these issues.…”
Section: Criteria 6: Is There Interest In Informed Deliberation About...mentioning
confidence: 99%
“…As with other cancers like breast or cervical cancers, the WHO recommends implementing CRC screening programs, and early detection effectively reduces the cancer burden on a country [19]. Previous studies advocate for Oman to adopt a CRC screening program [5,20,21].…”
Section: Review Criteria 1: Is the Health Problem Important?mentioning
confidence: 99%
“…39,46,47,54,[56][57][58][59][60][61][62][63][64][65][66][67] Furthermore, for colorectal cancer screening only, also disgust and worries about completing the faecal occult blood test (FOBt) incorrectly are additional barriers that should be carefully addressed. 68 Still considering the factor under the label "fears", some studies highlight those fears related to the screening in itself, namely fears related to the unknown procedure, 62,64 previous negative experiences, 66 test pain, 57,61 perceived mistrust in providers' confidentiality 63 and in the safety of the screening procedure. 67 However, nearly all the studies emphasize those "fears for the results", since many people consider cancer as a "deadly" diagnosis.…”
Section: Emotionsmentioning
confidence: 99%
“…67 However, nearly all the studies emphasize those "fears for the results", since many people consider cancer as a "deadly" diagnosis. 39,47,57,[61][62][63][64][65][66][67] In particular, when asked to think/recall about barriers to screening, some people often report future fears related to cancer diagnosis (e.g., fear of suffering, changes in appearance, and death). 69 Furthermore, research suggests that unwillingness to screen is also linked to fears about the impact of a potential cancer diagnosis on relationships, that is, losing friends/job, being stigmatized and isolated by the society and even by own family.…”
Section: Emotionsmentioning
confidence: 99%
See 1 more Smart Citation